XOTIN-QIZLARNI JISMONIY RIVOJLANISHIDA BADMINTON SPORT TURI VOSITA SIFATIDA - Samadova, O’ktabar (Физическое воспитание, спорт и здоровье, 2025)
Xaydarov, I. (2021). Ways to Prepare for the Profession by Inculcating a Healthy Lifestyle in the Minds of Students : Ways to Prepare for the Profession by Inculcating a Healthy Lifestyle in the Minds of Students . Физическое воспитание, спорт и здоровье, 5(5). извлечено от https://pshedu.jspi.uz/index.php/pshedu/article/view/4493 Xaydarov, I. (2022). YOSH GIMNASTIKACHILARDA MAXSUS-HARAKAT TAYYORGARLIGI KO‘RSATKICHLARINING DARAJASINI ANIQLASH. Физическое воспитание, спорт и здоровье, 5(5). извлечено от https://pshedu.jspi.uz/index.php/pshedu/article/view/4756 Xaydarov, I. (2021). Ways to Prepare for the Profession by Inculcating a Healthy Lifestyle in the Minds of Students : Ways to Prepare for the Profession by Inculcating a Healthy Lifestyle in the Minds of Students . Физическое воспитание, спорт и здоровье, 5(5). извлечено от https://pshedu.jspi.uz/index.php/pshedu/article/view/4493 Xaydarov, I. (2022). Zamonaviy voleybol o’yinida sakrovchanlikni rivojlantirishning dolzarbligi.: Zamonaviy voleybol o’yinida sakrovchanlikni rivojlantirishning dolzarbligi. Физическое воспитание, спорт и здоровье, 5(5). извлечено от https://pshedu.jspi.uz/index.php/pshedu/article/view/4992 o’g’li, N. E. Z. ., & o’g’li, X. I. S. . (2021). Ways to Prepare for the Profession by Inculcating a Healthy Lifestyle in the Minds of Students. Pindus Journal of Culture, Literature, and ELT, 1(12), 64–66. Retrieved from https://literature.academicjournal.io/index.php/literature/article/view/169 CREATING A HEALTHY LIFESTYLE FOR STUDENTS AT A YOUNG AGE | Web of Scientist: International Scientific Research Journal (academiascience.org) https://in-academy.uz/index.php/ejar/article/view/12369